Architecture Design of Intelligent Blockchain Consensus Algorithm in Digital Development of Sports Industry Chain - Wu, Zhong; Zhou, Chuan (2022 International Conference on Knowledge Engineering and Communication Systems (ICKES), 2022)
Blockchain has become a new technology development trend, and consensus algorithm, as the core technology of blockchain, has also received more and more attention and attracted extensive interest in the academic community. In order to solve the shortcomings of the existing research on the digital development of the sports industry chain, this paper discusses the concept of the sports industry, the composition of the sports industry chain, the blockchain architecture and the RDPoS consensus algorithm, and then investigates and discusses the consensus algorithm computing platform and node evaluation. The digital platform of sports industry chain is designed. And the application scheme of the intelligent blockchain consensus algorithm in the fund side privacy protection of the sports product industry chain sales system was designed. Through the experimental analysis of the algorithm throughput in the transaction process, the experimental data showed that the RDPoS algorithm throughput reached 1000 when the number of nodes was 100 and 125, which was better than the other two consensus algorithms. Therefore, the application of this algorithm in the framework of digital development of sports industry chain has a good effect.